HUBUNGAN PEMBERIAN KOMPRES HANGAT DENGAN PENGURANGAN NYERI DISMENORRHOE PRIMER PADA REMAJA PUTRI DI SMP USIA TAMA - suci nanda Tarigan (Fakultas Ilmu Kesehatan, 2022)
Adolescence is a period of transition from childhood to adulthood, usually from 10- 19 years. One of the signs of physical changes in young women will experience an increase in hormone levels that can cause the maturation of the breasts, ovaries, uterus and vagina and young women start menstruating. Menstruation begins between the ages of 12-15 years and lasts until the age of 45-50 years, one of the complaints most often felt by adolescents during menstruation is dysmenorrhea. The purpose of this study was to determine the relationship between giving warm compresses to reducing menstrual pain (dysmenorrhea) in adolescent girls at Tama Age Junior High School. This research is a Pre-experiment with One-Group Pre- test Post-test Design. The total population is 38 female students with a sample of 25 technical respondents. The sampling used is Accidental Sampling. The independent variable is a warm compress and the dependent variable is a decrease in menstrual pain (dysmenorrhea) in adolescent girls. Collecting data using a questionnaire sheet and Wilcoxon statistical test with = 0.05. The results showed that the dysmenorrhea pain scale before the warm compress was on the mild pain scale, namely 15 respondents (60%). And after doing a warm compress, the pain scale was 0 (no pain) i.e. 18 respondents (72%). The result of p value 0.000 (<0.05), so Ha is accepted. There is a relationship between giving warm compresses to reducing menstrual pain (dysmenorrhea) in adolescent girls at Tama Age Junior High School. One way that can be done to overcome dysmenorrhea is to apply warm compresses, which are done to meet the need for comfort, reduce or relieve pain, reduce or prevent muscle spasms and provide a warm feeling in the abdominal (stomach) area.